Tennyson and Goethe's faust - Baynes, Tom (Edinburgh : Edinburgh University Press, 2021)
Shows that Faust was a central influence on Tennyson's creative life.
Intro -- Acknowledgements -- Preface -- Abbreviations -- Introduction: Faust and British Literature, c. 1810-1892 -- I: The Death of Arthur Hallam -- 1 'I am to die already!': The Gretchen Tragedy -- 2 'To strive onwards': 'Ulysses', Progress and Trances -- 3 'Out of Orcus into Life': Hallam and Part Two -- II: Religion, Nature and Morality -- 4 'Two souls, alas, dwell in my breast': Religious Doubt -- 5 'Unveil thyself!': Faust and the Natural World -- 6 'The kiss of heavenly love': Saints and Sinners -- 'Last words' -- Conclusion -- Bibliography -- Index
Includes bibliographical references and index.
Description based on online resource; title from resource web page (Ebscohost Ebooks, viewed on December 09, 2021)
JSTOR
Keywords: Tennyson, Alfred Tennyson, -- Baron, -- 1809-1892 -- Criticism and interpretation; Goethe, Johann Wolfgang von, -- 1749-1832 -- Influence; Goethe, Johann Wolfgang von, -- 1749-1832.; Goethe, Johann Wolfgang von, -- 1749-1832; Tennyson, Alfred Tennyson, -- Baron, -- 1809-1892; Faust (Goethe, Johann Wolfgang von); English; Germanic & Scandinavian languages; C 1800 to c 1900.; Poetry by individual poets; Indo-European languages; Modern period, c 1500 onwards; Poetry; Languages; Time period; Literature & literary studies; LITERARY CRITICISM / European / English, Irish, Scottish, Welsh; Influence (Literary, artistic, etc.); Criticism, interpretation, etc